JA:2021-12. How to Increase ATV Safe Riding Behaviors in Youth: FFA Members from across the Country Respond. Issue 3 (2nd July 2020) - Jennissen, Charles; Stange, Nicholas; Wymore, Cole; Hooyer, Mitchell; Hoogerwerf, Pam; Mulford, Lauren; Denning, Gerene
ABSTRACT: Purpose : All-terrain vehicles (ATVs) are a significant source of rural injuries and deaths. Few studies have examined the best methods to improve adolescent ATV safety practices from the target audience's perspective. The study's objective was to explore youth's thoughts regarding how they might be best reached and persuaded to ride ATVs more safely. Methods : Attendees of three ATV safety workshop sessions at the 2018 National FFA Convention answered provided questions after facilitated discussion. Qualitative analysis of responses was independently performed by three research team members, and differences in coding were resolved through an iterative process. Descriptive and comparative analyses of responses were performed. Results/Findings : 309 FFA members from 62 clubs participated (29 states). Almost all clubs stated that one reason most youth don't ride ATVs safely is because of personal beliefs (e.g. inconvenient/not as enjoyable to ride safely). Almost three-fourths stated that an unsafe riding behavior young people would be most likely/willing to change was wearing a helmet. The safety behaviors that youth thought their peers would be least willing to change were traveling at lower speeds and not carrying passengers. Over one-half of the clubs stated that one of the best places to reach youth was at schools; the second most frequently mentioned was social media. Safety presenters that clubs felt youth would be most likely to listen to were peers and those just slightly older than the target audience. Other presentation groups frequently mentioned were crash survivors and those whose loved ones had been injured or died in ATV crashes. A variety of celebrities and authority figures were also suggested. Activities thought to be most effective at promoting safe riding were presentations with real-life injury examples including videos that might create a "fear factor, " and hands-on activities. FFA clubs responded that the least effective methods were lengthy, non-interactive presentations and printed materials with lots of facts/statistics. Practical Application : Youth have strong opinions regarding injury prevention information delivery, and what is likely to result in behavioral change. Our study provides important data regarding not only ATV safety information delivery, but other agricultural injury prevention messaging to youth as well.